Forecasting of Tourism Companies Before and During Covid-19 - Sarkar, Asima (Universitas Prasetiya Mulya, 2021)
For about last two years, the whole world is suffering from a novel disease i.e. Covid-19. When it was first diagnosed in China, even the giant health agencies could not predict the severity and spread of this disease. Slowly, when this novel corona virus had an outbreak the countries stopped all kinds of communication be it interstate or intercountry and so the tourism companies started facing huge loss due to lockdown in every single country. In this paper, the stock prices of the multinational tourism companies that operate in India, have been forecasted and using an online learning algorithm known as Gated Recurrent Unit (GRU). As we know that predicting stock prices is not an easy task to do, it requires extensive study of the stock market and intervention of statistical and machine learning models. We will try to spot whether the forecasting before pandemic is better than the forecasting during the pandemic for each of the six leading multinational tourism companies.